2021
DOI: 10.3389/fonc.2021.728740
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Adjuvant Immunotherapy With Cytokine-Induced Killer Cell for Hepatocellular Carcinoma Based on a Randomized Controlled Trial and Real-World Data

Abstract: BackgroundStudies using data from randomized controlled trials (RCTs) and real-world data (RWD) have suggested that adjuvant cytokine-induced killer (CIK) cell immunotherapy after curative treatment for hepatocellular carcinoma (HCC) prolongs recurrence-free survival (RFS) and overall survival (OS). However, the cost-effectiveness of CIK cell immunotherapy as an adjuvant therapy for HCC compared to no adjuvant therapy is uncertain.MethodsWe constructed a partitioned survival model to compare the expected costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
(54 reference statements)
0
8
2
Order By: Relevance
“…913 In a cost-effectiveness analysis study based on the results of the randomized controlled study and the realworld study, the incremental cost-effectiveness ratio were $33,077/QALY (quality-adjusted life-year) and $25,107/QALY, respectively. 814 In a Chinese randomized controlled phase 3 trial, CIK cell treatment significantly prolonged the time-torecurrence (13.6 months in the CIK group and 7.8 months in the control group, P=0.01); however, in this study, no statistically significant differences were observed in either RFS or OS. 907 A meta-analysis of the RCTs reported that adjuvant CIK cell therapy significantly improved RFS and OS up to 3 years in patients after curative treatment.…”
Section: Adjuvant Therapycontrasting
confidence: 56%
See 3 more Smart Citations
“…913 In a cost-effectiveness analysis study based on the results of the randomized controlled study and the realworld study, the incremental cost-effectiveness ratio were $33,077/QALY (quality-adjusted life-year) and $25,107/QALY, respectively. 814 In a Chinese randomized controlled phase 3 trial, CIK cell treatment significantly prolonged the time-torecurrence (13.6 months in the CIK group and 7.8 months in the control group, P=0.01); however, in this study, no statistically significant differences were observed in either RFS or OS. 907 A meta-analysis of the RCTs reported that adjuvant CIK cell therapy significantly improved RFS and OS up to 3 years in patients after curative treatment.…”
Section: Adjuvant Therapycontrasting
confidence: 56%
“…It is recommended to interrupt lenvatinib if 24hour urinary protein is ≥2 g. If a dipstick proteinuria result of 2+ or more is detected, a random urinary protein to creatinine ratio can be used to monitor proteinuria before further testing with the 24-hour urinary protein. 813,814 Thyroid stimulating hormone (TSH) levels should be monitored. If the TSH level is higher than 10 mIU/L or higher than 5 mIU/L on two separate occasions, consultation with an endocrinologist should be considered.…”
Section: Lenvatinibmentioning
confidence: 99%
See 2 more Smart Citations
“…Other adverse events frequently observed in the lenvatinib group were diarrhea (39%), anorexia (34%), weight loss (31%), fatigue (30%), proteinuria (25%), and hypothyroidism (16%). It is recommended to interrupt lenvatinib if 24-hour urinary protein is ≥ 2 g. If a dipstick proteinuria result of 2+ or more is detected, a random urinary protein to creatinine ratio can be used to monitor proteinuria before further testing with the 24-hour urinary protein [ 813 814 ]. Thyroid stimulating hormone (TSH) levels should be monitored.…”
Section: Systemic Therapiesmentioning
confidence: 99%